Design framework of unreal engine for VR animation space analysis - Kim, Dong-Jo; Kim, Young-Nam (Edelweiss Applied Science and Technology, 2025)
Unreal Engine has emerged as a leading platform for virtual reality (VR) development, offering advanced tools to enhance immersive virtual environments and user interaction. This study examines the key technological features of Unreal Engine that contribute to realism and interactivity in VR, focusing on real-time rendering, photorealistic graphics, and precise physical responsiveness. Adopting a technical analysis approach, this research evaluates the impact of key technologies, including hand tracking, real-time ray tracing, and in-camera visual effects (ICVFX), on interaction fidelity and visual realism. The findings indicate that hand tracking enables natural, gesture-based interactions without the need for external controllers, while real-time ray tracing significantly improves lighting accuracy, thereby enhancing the overall visual fidelity. Additionally, 3D spatial audio refines auditory perception by providing accurate sound directionality and depth, further augmenting user immersion. ICVFX facilitates the seamless integration of live-action footage with virtual environments, expanding the potential for realistic storytelling in VR animation and virtual production. In conclusion, despite the complexity of Unreal Engine’s interface, the VR template system and OpenXR support simplify development and enhance cross-platform compatibility. The study highlights Unreal Engine’s scalability for large-scale VR projects and its transformative potential across industries such as gaming, simulation, education, and virtual production. The practical implications suggest that leveraging Unreal Engine’s capabilities can lead to more immersive, interactive, and efficient VR content creation, paving the way for future advancements in virtual experience design.